Review: Acts of the International Congress: Comparative Liturgy Fifty Years after Anton Baumstark (1872–1948). Rome, 25–29 September 1998 - Day, Juliette ca. 20./21. Jh. (The journal of theological studies, 2005)
Acts of the International Congress: Comparative Liturgy Fifty Years after Anton Baumstark (1872–1948). Rome, 25–29 September 1998 Robert F. Taft SJGabriele Winkler 1,020 (Orientalia Christiana Analecta, 265.)Rome Pontificio Istituto Orientale 2001 88 7210 333 9 Paper